Analisis Problematika Pembelajaran Sejarah Kebudayaan Islam (SKI) di Madrasah Aliyah - Ariyanti, Novi; Anggerawati , Nuke Ladyna (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Learning Islamic Cultural History (ICH) is crucial for shaping students character through moral, spiritual, and social values. However, its effectiveness is hindered by dominant lecture methods, inadequate learning media, and low student enthusiasm. This study aims to identify the specific problems encountered in learning islamic cultural history, focusing on teachers and students perceptions and the underlying factors contributing to these issues. Employing a qualitative method with a case study approach, the research utilizes interviews, observations, and documentation for data collection. Data analysis follows the Miles and Huberman model, which includes data reduction, presentation, and conclusion formulation. The findings indicate that students find Islamic history learning uninteresting and difficult to grasp due to irrelevant material, while teachers struggle to convey complex content within limited time and resources. The prevalent use of lectures has proven ineffective, with interactive methods like discussions and role-playing rarely utilized, leading to students’ difficulties in comprehension and low motivation. Additionally, the availability of learning resources, such as encyclopedias, and a reading culture among students are underdeveloped. To address these challenges, the Head of Madrasah and teacher have initiated reading corners in classrooms stocked with Islamic cultural history books and encouraged the use of social media for assignments.